International Comparisons of Tax and Transfer Progressivity: New Evidence from the Luxembourg Income Study - John Bishop; Paul Thistle; John Formby (Luxembourg Income Study (LIS), 1990)
This paper applies an extended Lorenz dominance welfare principle to make and compare estimates of the overall progressivity of taxes and transfers for Australia, Canada, Sweden, and the U.S.
Keywords: 330